Particulate Matter During Food Preparation on a Barbecue: A Case Study of an Electric Barbecue - Jan Stefan Bihałowicz; Artur Badyda; Wioletta Rogula-Kozłowska; Kamila Widziewicz-Rzońca; Patrycja Rogula-Kopiec; Dmytro Chyzhykov; Grzegorz Majewski; Mariusz Pecio (Applied Sciences)
The distribution of mass and the number of particles is a determining factor in the respirable nature of a given particulate matter (PM), and thus in the potential health effects of breathing the air in question. One of the most popular activities during the summer months is the preparation of food on a barbecue. Barbecuing represents one of the few sources of combustion particulates during the summer, a period which is otherwise characterised by a lack of heating. The objective of this study is to ascertain the fractional composition of PM emitted during food preparation on an electric barbecue and to compare these values with the measured background. The concentrations of particulate matter (PM) at the barbecue were determined with a Palas AQ Guard optical spectrometer, while the background concentrations were measured with a Palas Fidas 200 optical spectrometer that complies with the EN16450 standard. The contribution of the individual PM fractions measured in the barbecue environment differed from that observed in the ambient air. The background measurements exhibited a relatively well-defined and consistent distribution, with the PM1 fraction representing between 10 and 30% of the PM mass and the PM4−1 fraction accounting for only 10 to 20%. Thus, the mass of the PM4 fraction did not exceed 50% of the total mass of particles. Upon analysis of the particles emitted during the grilling process, it was observed that the PM1 fraction was capable of accounting for a substantial proportion, exceeding 90% of the PM mass. The trend related to the PM4−1 fraction was maintained; however, the limit of the maximum content of this fraction increased to 40% of the PM. The results demonstrate that the barbecue process itself, utilising a barbecue without emission fuel, can exert a notable influence on the contribution of submicron PM.